Nanomaterials for electrochemical energy storage: the good and the bad - Maria Rosa Palacin; Patrice Simon; Jean Marie Tarascon (Acta Chimica Slovenica, 2016)
A critical view on the outcome of research in nanomaterials for electrochemical energy storage devices (batteries and supercapacitors) is provided through selected examples. The nano- approach traces back to the early battery research and its benefits realized even before the nano- term was coined  and has enabled important progress which have translated, for instance, in the possibility of using LiFePO4 as electrode material.  On the other hand, the nano- approach has also been oversold at all levels and hence some examples are also shown on the detrimental side effects of the use of nano-materials which should be taken into account if steady progress to result in practical benefit is to be made.